GAYA RETORIKA BAGIAN METODOLOGI PENELITIAN PADA JURNAL NASIONAL TERAKREDITASI BIDANG SOSIOLOGI - Fitria Dinanti, Netty; Puspita, Rini; Armayani, Septi; Fitriani, Wiza; Arono, Arono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Each writing has its own rhetorical style or characteristics in its description, as well as in the writing on the methodology section of research journal article (AJP) in the field of sociology. This study examines the rhetorical style in the stages (moves) in 23 articles from two research journals in sociology, namely the Journal of Sociology of Society an the Journal of Social Religion. This research methodology uses a qualitative approach with a descriptive method. This research was conducted in Bengkulu, in November – Desember 2021. The data collection technique was using observation techniques. The purpose of this study is to describe the result of the study or rhetorical style on the aspects of the stage (move) in research juournal articles in the field of sociology. The result showed that the most dominant stage used in research journal articles in the field of sociology were Stage 1 (Introduction to the study), Stage 2 (Research subject) and Satge 3 (Research procedur). In research journal articles in the field of sociology is that they predominantly use data collection techniques in the form of observations, interviews, and documentation.